Portfolio selection and performance using active and passive strategies (Assessing SRI-KEHATI index in 2013-2018) - Riko Hendrawan; Nurul Rachma Fadhyla; Wiwin Aminah (Jurnal Siasat Bisnis, 2020)
This purpose of this study is to examine the simulation results of optimal stock portfolio establishment with active and passive strategy using Tobin’s Qand PBV ratio approach in Sri Kehati Index. We used data from the annual financial reports in 6years2013-2018, and each period, the portfolio was constructed in six fragments; High Tobin’s Q, Medium Tobin’s Q, Low Tobin’s Q, High PBV, Medium PBV and Low PBV.  We used Sharpe, Treynor, and Jensen method to measure the portfolio performance and we adjusted for active and passive portfolio strategy and evaluated in each respective period. Finding from this research shows that on passive strategy, the total average of accumulated return is 78.3576%.  The low Tobin’s Q portfolio is followed by low PBV, and high PBV has a return value above the total average and above the IDX Composite. While the total average of the accumulated risks in the passive strategy is 23.4193%. Furthermore based on the results of the performance comparison between return and risks from the portfolio and IDX Composite as a market, in general, both are on passive and active strategies. The results also show that the low Tobin’s Q portfolio is consistently able to provide the highest return value, although the low Tobin’s Q portfolio consistently provides the highest risk both on passive and active strategies; thus, there is a consistently between the results of research and the theory of high-risk, high return. Meanwhile the high PBV portfolio, in general, is consistently able to provide a high return, and risk values are consistently at the lowest level compared to other portfolios. The result shows that it has reached the purpose of establishing a stock portfolio